Mewujudkan New Public Management Terhadap Indisipliner Mahasiswa Melalui Penerapan AbCD (Absen Cap Driji) - Hayat Hayat; Abid Zamzami (Jurnal Inovasi Hasil Pengabdian Masyarakat (JIPEMAS), 2019)
University of Islam Malang (UNISMA) as a public institution has a goal to be achieved. One of the goals that Unisma wants to achieve is to produce superior and qualified students. To achieve this goal, Unisma should apply new policies in terms of New Public Management (NPM). In NPM, Unisma should apply Absen Cap Driji / Absensi Sidik Jari (AbCD) machines as a solution to overcome student indiscipline. Need to know, so far the form of student indiscipline in Unisma has always increased every year.This form of indiscipline, among others; 1) Often come late, 2) Do not do assignments, 3) Often do not enter without reason, 4) D3C (Come, Sit, Listen, and underestimate the lecture. If the form of student indiscipline is unchecked, it is feared that students are increasingly out of control, affecting other students, even Unisma fails to achieve the goal of creating excellent and high quality students. So that AbCD machines are needed in order to implement NPM while minimizing student indiscipline. AbCD is an absent machine that uses fingerprints so as to reduce dishonesty done by students in terms of college attendance. AbCD replaces the previous presence system which is still manual and easily manipulated. This AbCD program is expected to provide benefits in the long term, those are: 1) To discipline Unisma students by applying AbCD machines, 2) To develop IT in Unisma so as not to be left behind, 3) To avoid conflicts between students and students, and students with lecturers at Unisma. The methods used in implementing AbCD machines are: 1) Pre-Program Analysis, 2) Location Survey, 3) Licensing Administration, 4) Procurement of Goods, 5) Material Preparation, 6) Recruitment of Facilitators and Participants, 7) Lecturer debriefing, 8 ) Student Counseling, 9) Utilization of AbCD, and 10) Evaluation. Which of the ten methods of implementation has been completed with the budget and implementation schedule.